2017
DOI: 10.1002/mp.12447
|View full text |Cite
|
Sign up to set email alerts
|

Development of patient‐controlled respiratory gating system based on visual guidance for magnetic‐resonance image‐guided radiation therapy

Abstract: The developed system could improve treatment efficiency when performing respiratory-gated MR-IGRT. The VG-PC gating system could be applied to any kind of bore-type radiotherapy machine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…During gated delivery, patients were provided with visual guidance via an in-room screen displaying the live sagittal cine-MR image with an overlay of gating target and boundary, thus enabling them to steer their repeated breath-holds to the right position. This idea was adopted from other published in-room screen solutions for MRgRT [17,20]. Patients were able to observe this monitor during the whole treatment with the help of a mirror fixed to the bore (see Fig.…”
Section: Treatmentmentioning
confidence: 99%
“…During gated delivery, patients were provided with visual guidance via an in-room screen displaying the live sagittal cine-MR image with an overlay of gating target and boundary, thus enabling them to steer their repeated breath-holds to the right position. This idea was adopted from other published in-room screen solutions for MRgRT [17,20]. Patients were able to observe this monitor during the whole treatment with the help of a mirror fixed to the bore (see Fig.…”
Section: Treatmentmentioning
confidence: 99%
“…In order to visually guide patients especially for repeated breath-holds, some authors have reported on in-room screens or projectors [28], [29]. During RT delivery, the patients can thereby see their live cine MR images including projections of target and margin, and thus actively control their breathing.…”
Section: Treatment Planning and Deliverymentioning
confidence: 99%
“…In this setting, the breath-hold technique has proven to be a safe and effective way to reduce tumor motion, resulting in an average intrafractional movement of <1 mm in all directions and an average cranio-caudal interfractional reproducibility of <4 mm ( 79 , 80 ). Some authors reported on the implementation of an additional visual feedback for the breath-hold procedure using in-room screens or projectors ( 81 , 82 ). This allows patients to see their live cine MR images including projections of target and gating boundary and, thus actively control their breathing.…”
Section: Motion Management For Liver Mrgrtmentioning
confidence: 99%